Application of microencapsulated Trichoderma spp. against Moniliophthora roreri during the vegetative development of cocoa - Avilés, Daniel (2023)
Ecuador is one of the leading producers of fine aroma cocoa worldwide, involving around 100,000 producer families. On the American continent, the largest producer is Brazil, with 18%, followed by Ecuador and Colombia, and it is estimated that more than 20 million people depend directly on this crop. Moniliophthora roreri, the causal agent of frost pot rot, has been a cause of great concern due to the production losses it has caused, which in 2022 amounted to 80% in different cocoa-producing provinces of Ecuador and worldwide losses of 30% performance they are estimates. This study aimed to determine the biological control potential of microcapsules made with Trichoderma spp spore solution against M. roreri. The In vitro evaluation of the microcapsules did not show significant results in the percentage of inhibition, and this was not the case in the direct evaluation on the farm, where the severity in the 15-day-old fruits showed 0% external and internal affectation with the use of microcapsules in its liquid presentation. Additionally, the evolution of the microcapsules in 28-day-old fruits was observed in severity from 1 to 25% with intercalated applications. Beneficial fungi were applied first, followed by pathogens; though, when the pathogen was applied first, and then the beneficial fungus, the increased severity of external and internal disease was 26-75% and 80-100%, respectively. In conclusion, using microcapsules based on Trichoderma strains at the early ages of the fruits generates protection against M. roreri throughout the vegetative development of the fruit.